Технічні аспекти впровадження джерел розподільної генерації в електричних мережах - Кириленко, О.В.; Павловський, В.В.; Лук'яненко, Л.М. (Технічна електродинаміка, 2011)
The main technical problems relating to adoption of distributed generation sources in electric mains of Ukraine have been considered. The concept definition of distributed generation has been given. The analysis of effect of distributed generation on reliability, rating of electric energy quality and losses in electric mains, construction of relay protection and automation systems has been performed. The features of designing and operation of electric mains have been indicated. The measures which should be taken by adoption of distributed generation sources have been assigned.